Operation Barbarossa : Nazi Germany's war in the east, 1941 - 1945 - Hartmann, Christian 1959- (Oxford University Press, 2013)
"The war between Nazi Germany and Stalin's Soviet Union that raged between 1941 and 1945 was unprecedented in the scale of the destruction that it wrought and the deep scars that it left behind. The invasion of the Soviet Union was the conflict that Hitler had always ultimately planned for in his dream of creating a 'Thousand Year Reich'. From the beginning it was a struggle for survival, conducted with great bitterness and savagery by opponents who knew that defeat meant the destruction of everything they stood for. ... Enriched by a wealth of eye-witness testimony from both the Soviet and the German sides, Operation Barbarossa paints a masterly overview of these momentous four years and their human consequences - one that is both gripping and deeply moving." -- Publisher website